The growth and development of metropolitan planning strategies in Istanbul - Sebnem Yuzer; Salim Kucuk (European Regional Science Association (ERSA), 1998)
Beside it?s historical, cultural and natural values in the international level, Istanbul is a world wide city which leads to national and regional development from socio-economic point of view. However, there are some obstacles to become an international metropolis. The two properties which have determined the growth dynamics negatively up to now are: ? Turkey?s industrialisation occurs mainly in Istanbul and the development of the city as an Industrial City, ? In a rapid and unhealthy developed city, the pressure of economic process base on speculations on real estates and other urban areas over business and political decision mechanism. Istanbul, with it?s approximately 9 million inhabitant, pulls a great amount of migrant every year. However, inadequacy in present infrastructure, housing stock and natural life sources which answer to migrants, leads to a complex structure in the city. There are some obstacles to become an international metropolis. The two properties which have determined the growth dynamics negatively up to now are: Istanbul Metropolitan Area Sub Region Master Plan done by Greater Municipality of Istanbul in 1995, aimed Istanbul to be a historical, cultural, scientific, artistic and service city integrated with regional countries and to take part in the hierarchy of world metropolitan cities in the current economic development process. According to this aim, Greater Municipality of Istanbul developed a strategic plan as a result of planning studies which direct city development. With this plan, ? Planning decisions in the metropolitan area that supply balanced land use for the protection of natural sources, cultural heritage and sustainable environment are formed. ? Transportation schema that ideally organises relations among the most convenient centre and sub-centres of Istanbul?s linear development, We are aimed to explain Istanbul Metropolitan Area Sub Region Master Plan.
Keywords: 330